2002
DOI: 10.1007/bf03190401
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, distribution and excretion of3H-labeled cephaeline- and emetine-spiked ipecac syrup in rats

Abstract: The maximum plasma radioactivity levels of tritium (3H)-labeled cephaeline, (24.3, 28.7 and 40.6 ng eq./mL) were reached at 2.00-3.33 hours following oral dosing of ipecac syrup. The maximum plasma radioactivity levels of 3H-emetine (2.71, 6.47 and 9.62 ng eq./mL) were reached at 1.08-2.33 hours following ipecac syrup administration. The Cmax values of 3H-cephaeline were followed by a biexponential decrease with half-lives t 1/2(lambda z) of 3.45-9.40 hours. On the other hand, the t 1/2 (lambda z)of 3H-emetine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…At 12 h (T max ) the concentration reached to maximum of 1.61 μM and then gradually decreased to 0.36 μM at 72 h which was still much higher than the EC 50 (7 nM) for inhibition of virus replication. This was in accordance with the previous study with Ipecac syrup that Emetine could be enriched in the tissues such as lung [16], which was especially important for the COVID-19 since the lung was the major target tissue of the SARS-CoV-2 virus. In mice a similar trend was observed and at 12 h the maxium concentration (1.8 μM) was reached in the lung and gradually decreased to 0.23 μM which was still 30-fold higher than the EC 50 for the inhibition of virus replication ( Fig.…”
Section: In Vivo Pharmacokinetic Study Of Emetinesupporting
confidence: 93%
See 1 more Smart Citation
“…At 12 h (T max ) the concentration reached to maximum of 1.61 μM and then gradually decreased to 0.36 μM at 72 h which was still much higher than the EC 50 (7 nM) for inhibition of virus replication. This was in accordance with the previous study with Ipecac syrup that Emetine could be enriched in the tissues such as lung [16], which was especially important for the COVID-19 since the lung was the major target tissue of the SARS-CoV-2 virus. In mice a similar trend was observed and at 12 h the maxium concentration (1.8 μM) was reached in the lung and gradually decreased to 0.23 μM which was still 30-fold higher than the EC 50 for the inhibition of virus replication ( Fig.…”
Section: In Vivo Pharmacokinetic Study Of Emetinesupporting
confidence: 93%
“…In order to obtain an envision for the clinical translation, we then tried to examine the pharmacokinetic (PK) profiles of Emetine in the preclinical in vivo models. Although there has been some random PK studies either with Emetine itself or Ipecac syrup (containing Emetine) [ 15 , 16 ], in order to obtain the detailed PK spectrum, we first systematically investigated Emetine in different species including mice, rats and beagle dogs to depict an overall picture (Table 1 ). The results showed that in mice and rats, oral administration of Emetine reached maximum concentration (C max ) in the blood plasma in a relatively long time (T max : 1.67 h and 9 h for the mice and rats respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, another advantage of intramuscular over oral administration could be its greater uptake by the lungs. With radiolabeled emetine given by the oral route in rats, there was, at most time points, significantly (0.8-5.8 times) more emetine found in the liver than there was in the lungs [11]. Conversely, with radiolabeled emetine given by the intraperitoneal route in guinea pigs, the situation was reversed; at each time point, there was over twice as much emetine in the lungs than the liver [16].…”
mentioning
confidence: 93%
“…In relation to the lungs, after 8 and 24 h, the concentration of emetine in the lungs is~173 and~294 times higher than in plasma, respectively, with the maximum recorded amount present in the lungs at the 24-h time period. High concentrations were also found in many other tissues, such as the liver, heart, and small and large intestines [11]. Similarly, studies in humans have strongly indicated that emetine quickly undergoes extensive distribution to the tissues [9], with slow excretion and detectable concentrations that may persist in the urine for 40-60 days after treatment has been ceased [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation